PERWUJUDAN INDONESIA LAYAK ANAK (Studi Kasus PKBM Kasih Bundo Kota Bukittinggi Sebagai Penyelenggara Pendidikan Kesetaraan) - Eka Pasca Surya Bayu; Dewi Sari Wahyuni (State Institute of Islamic Studies Batusangkar, 2019)
Education must be carried out for it provides services for all people. Thus, Indonesian government conducts various policies. One of them is child-friendly city. This article has a purpose to explain the other side of education which facilitated Bukittinggi as one of child-friendly city in Indonesia. This research was carried out at PKBM Kasih Bundo, Bukittinggi. The research method is descriptive research. The research findings reflect some activities done by PKBM Kasih Bundo Bukittinggi in realizing Bukittinggi as child-friendly citiey, namely 1) organizing alternatives education, 2) services of child victim of human trafficking, 3) services of child victims of drugs and sex violence, and 4) services for children deviant behavior.